Pengaruh Kompetensi Kepemimpinan dan Supervisi Kepala Sekolah terhadap Kinerja Guru SMP di Kabupaten Nagekeo - Kristoforus Buku; Achadi Budi Santosa; Sukirman Sukirman; Enung Hasanah (Edumaspul: Jurnal Pendidikan, 2021)
The purpose of this study was to determine the effect of the principal's leadership competence and the implementation of supervision by the principal on the performance of junior high school teachers in Nagekeo Regency, East Nusa Tenggara Province. Questionnaire with closed statement items was used as an instrument in this study with a quantitative descriptive approach. The questionnaire uses a Likert scale, and its validity and reliability have been tested. Simple regression is used to see the effect of each independent variable on the dependent variable while multiple linear regression is intended to see the effect of the independent variable on the dependent variable simultaneously. The results showed a positive and significant influence between the principal's leadership competence on teacher performance by 50.5%. Principal supervision also has a positive and significant effect on teacher performance, with a percentage of 43.6%. The positive and significant effect is simultaneously shown by the leadership competence of the principal and the supervision of the principal on teacher performance with a percentage of reaching 70.4%.